Antifungal Activity and Composition of Essential Oils of Conyza canadensis Herbs and Roots. (1st May 2012) - Veres, Katalin; Csupor-Löffler, Boglárka; Lázár, Andrea; Hohmann, Judit
Abstract : Essential oils from herbs and roots of Conyza canadensis (horseweed), collected in Hungary, were obtained by hydrodistillation. The chemical compositions of the oils were analysed by combination of GC and GC/MS. The major constituent of the oil obtained from the aerial parts of horseweed was limonene (78%), while the main component of root oil was 2 Z, 8 Z -matricaria ester. The antimicrobial activities of the oils were tested on Gram-positive ( Enterococcus faecalis, Staphylococcus aureus, and Streptococcus pyogenes ), Gram-negative ( Escherichia coli, Pseudomonas aeruginosa ) bacteria, reference fungal strains, and fungal strains isolated from patients ( Candida, Cryptococcus, Trichophyton, Rhodotorula, and Aspergillus ) by agar disc diffusion and broth dilution methods. None of the oils showed any activity against the tested bacterial strains, but exhibited moderate-to-strong activity against all fungi with the only exception of A. fumigatus . The highest zone of inhibition was observed in case of Cryptococcus neoformans and Trichophyton interdigitalis